Incorporating stakeholder perspectives into the assessment and provision of captive elephant welfare - Chadwick, C.L.; Williams, E.; Asher, L.; Yon, L. (Universities Federation for Animal Welfare, 2017)
Recent concerns over the welfare of elephants in UK zoos have implications for their future in captivity, and it is clear that improvements in welfare should be made. Evidence suggests that the knowledge of experienced stakeholders is vital to captive animal welfare assessment. However, there have been few attempts to consult with zoo personnel and other stakeholders on the assessment of elephant welfare, and much of their valuable knowledge of routine husbandry has not been captured in the published literature. As part of a research project commissioned by the Department for Environment Food and Rural Affairs, open response focus groups and workshop discussions were conducted with representatives from 15 UK elephant-holding facilities, and other experts in the welfare and behaviour of captive or free-ranging elephants. Participants described three broad categories of welfare indicators: behavioural, physical and physiological. Resources perceived to be of importance to elephants included aspects of the physical environment, such as feeding opportunities and appropriate substrate, and aspects of the social environment, including group size and relatedness. The data obtained during this study can be used to develop an elephant welfare assessment strategy, informed by the knowledge and expertise of experienced stakeholders, and for consideration of potential changes to guidelines for managing elephants in captivity. Our approach to capturing the views of those who work closely with captive species could be applied elsewhere, in order to draw upon the extensive knowledge of expert stakeholders and consider ways to improve the welfare of captive animals.